Malaysia as wedding destination: perception and destination characteristics / Muhammad Hafizi Zamri - Zamri, Muhammad Hafizi (2013)
Wedding is once-a-life event in people's life. Comparing with the other personal events, such as birthday and anniversaries, wedding is more complex, because it involves friends and families and a range of related service activities covering from catering to entertainments and selection of venue. As of today, there are very limited studies regarding the arrival of international tourists for wedding event purposes in Malaysia. Therefore, this study intends to identify the perception of international bridal tourists on Malaysia as their chosen wedding destination. It also aims to find out the most significant characteristics towards the arrival of international wedding bridal couples to have their wedding events in Malaysia. A qualitative approach was considered to be the most effective research method and semi structured interview was used in getting information from the potential couples. This research conducted semi structured online and face to face interviews with nine international bridal couples. Findings clearly revealed that the uniqueness of Malaysian culture and the wedding venue are the main factors why these international bridal tourists choose Malaysia as their wedding destinations. This study provides great benefits towards local event planners especially professional wedding planners on the potential of leveraging the local resources as a wedding tourism destination. Results of the study is useful for maintaining and upgrading of the potential factors to more advance level and could generate more income and indirectly helping to promote Malaysia as a bridal tourism hub among the international bridal couples.